Analysis of Dispensing Errors Made by First-Year Pharmacy Students in a Virtual Dispensing Assessment - Sara Chuang; Kate Lorraine Grieve; Vivienne Mak (MDPI AG, 2021)
Pharmacists have a crucial role in the supply of medications and ensuring optimal patient outcomes. However, with the increased use of prescription medications, there is a potential for dispensing errors to occur. Some dispensing errors can result in patient harm, with some leading to death. The development of safe and accurate dispensing skills in pharmacy students is an essential part of the pharmacy curriculum to prevent such dispensing errors from occurring. A retrospective study was conducted on a virtual dispensing assessment completed by first-year pharmacy students using MyDispense at Monash University. Students were assessed on their ability to safely and accurately dispense four prescriptions. The students' answers in the assessment were then analyzed using qualitative and quantitative methods. Errors in drug quantity, number of repeats, product, patient and prescriber selection were quantitatively analyzed. Through the development of a codebook, frequency of errors was determined for label directions and appropriate use of ancillary labels. In this study, the dispensing errors that were identified depended on the class of medication. Errors in label directions were most common, with the majority of errors displaying incorrect route of administration, drug formulation and/or frequency of dosing. Identified errors were then further categorized into potential severity of harm, ranging from "no harm" to "severe harm". The findings from this study show the types of errors made by students that are preventable and the potential for first-year pharmacy students to benefit from more comprehensive introductions to dispensing guides and safe environments to practice.